Modelling hydrodynamic drag in swimming using computational fluid dynamics - Marinho, D.A. (2010)
In the sports field, numerical simulation techniques have been shown to provide useful information about performance and to play an important role as a complementary tool to physical experiments. Indeed, this methodology has produced significant improvements in equipment design and technique prescription in different sports (Kellar et al., 1999; Pallis et al., 2000; Dabnichki & Avital, 2006). In swimming, this methodology has been applied in order to better understand swimming performance. Thus, the numerical techniques have been addressed to study the propulsive forces generated by the propelling segments (Rouboa et al., 2006; Marinho et al., 2009a) and the hydrodynamic drag forces resisting forward motion (Silva et al., 2008; Marinho et al., 2009b). Although the swimmer’s performance is dependent on both drag and propulsive forces, within this chapter the focus is only on the analysis of the hydrodynamic drag. Therefore, this chapter covers topics in swimming drag simulation from a computational fluid dynamics (CFD) perspective. This perspective means emphasis on the fluid mechanics and CFD methodology applied in swimming research. One of the main aims for performance (velocity) enhancement of swimming is to minimize drag forces resisting forward motion, for a given trust. This chapter will concentrate on numerical simulation results, considering the scientific simulation point-of-view, for this practical implication in swimming. In the first part of the chapter, we introduce the issue, the main aims of the chapter and a brief explanation of the CFD methodology. Then, the contribution of different studies for swimming using CFD and some practical applications of this methodology are presented. During the chapter the authors will attempt to present the CFD data and to address some practical concerns to swimmers and coaches, comparing as well the numerical data with other experimental data available in the literature.